A modular two yeast species secretion system for the production and preparative application of unspecific peroxygenases - Pascal Püllmann (Nature Portfolio, 2021)
Püllmann et al developed a modular Golden Gate-based secretion system, which enabled production and one-step purification of active fungal unspecific peroxygenases (UPOs) in yeast. Their system was applied to an enantioselective conversion on a preparative scale and may be used in the future for other genes of interest that are suitable for production in yeast.